Effect of Cigarette Smoking on Vitamin C in Non Pregnant and Pregnant Women - Ankita Khandolkar; Rakesh Kumar Jha; Pradip Jain; Archana Dhok (Institute of Medico-legal Publications Pvt Ltd, 2021)
Introduction: It is perceived that smoking cigarettes during pregnancy is unfortunate and can promptexpanded unconstrained early abortion in the first trimester, premature abruption of the placenta, pretermdelivery, decreased birth weight and SIDS. All things considered, children destined to mothers who smokeduring pregnancy weigh 150-300 gram not exactly those destined to mothers who don’t smoke and thedanger of little for-gestational age among ladies who smoke is at any rate twice as high as among ladieswho don’t smoke. For more seasoned ladies, the effect of smoking during pregnancy on fetal developmentand preterm conveyance are more noteworthy. The danger of placental issues can be expanded by long haulsmoking.Aim: Effect of cigarette smoking in non-pregnant and pregnant women’s on the blood serum level of vitaminCMaterial and Methods: The present study included 150 subjects of age group 25-35 years. Out which75 werenon-smokers pregnant women as a control group and 75 were smoker pregnant women as a studygroup. During this stage of pregnancy, the vitamin C levels in the maternal serum were colorimetricallydetermined. The respondents also answered a questionnaire about their smoking habits during pregnancy.Vitamin C intake was measured during the third trimester by monitoring food consumption over a 5-dayperiod (including Sunday) and vitamin C registration with dietary supplements.Results: In the present study, we found significant decreased levels of serum vitamin C and in pregnantcigarette smokers as compared to pregnant non-smokers.Vitamin C was protective for placental abruption innonsmokers but not in smokers (P=0.01).Conclusion: If the production of antioxidants (vitamin C) in smokers is lower compared to pregnant womenwho are not smokers, this could aggravate their newborn’s peroxidation problems. Supplementation ofvitamin C tends to be connected with a decrease in placental abruption and preterm birth in pregnant smokers.